Career Women in Tafsir Al Misbah: An Analytical Study of Fazlur Rahman's Double Movement Theory - Taskia Uswatun Khasanah; Ainur Rhain; Kharis Nugroho; Ahmad Nurrohim; Muhammad Abuzar (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective:  This study aims to examine contemporary issues regarding career women from the perspective of Qur'anic interpretation. The main focus is to examine Quraish Shihab's views in Tafsir Al-Misbah on women working in the public sphere, as well as analyze them through the theory of double movement developed by Fazlur Rahman. Theoretical framework:  Using Fazlur Rahman's theory of double movement, which emphasizes historical analysis of verse and its reinterpretation in contemporary social contexts, to understand the role of women in Islam in a relevant way. Literature review: Previous studies are still dominant in normative and fiqh. This study fills the gap by combining Fazlur Rahman's theory and contemporary interpretation of Quraish Shihab in discussing career women thematically. Methods:  Using a qualitative method based on literature study, with the main source of Tafsir Al-Misbah and literature on the theory of double movement. The analysis was carried out in a descriptive-analytical manner. Result:  The results of the study show that both Quraish Shihab and Fazlur Rahman support women's right to have a career and contribute to the public sphere, while maintaining Islamic Sharia values. In his commentary, Quraish Shihab emphasizes that Islam does not prohibit women from working, as long as they adhere to the moral and ethical principles set by the religion. Implications: This contextual interpretation can be a theological foundation in supporting gender equality and the participation of Muslim women in the workforce. Novelty: Integrating the theory of double movement with the interpretation of Quraish Shihab, specifically in the issue of career women, offers a new approach in the study of contemporary thematic interpretation.